Qualitative and quantitative evaluation of nourishing consumption of physically active women - Luciana Rossi; Ana Paula Tanaka Hayashi; Marina Yazigi Solis; Rebeca Lugaresi Lugaresi; Naiara Almeida; Sophia Cornbluth Szarfarc; Sônia Tucunduva Philippi (O Mundo da Saúde, 2011)
Abstract: This study aimed to evaluate quantitatively and qualitatively the nourishing consumption of physically active women in order to investigate their nourishing style and to weave recommendations of nourishing consumption base on the Brazilian Nourishing Pyramid. For that, we selected, in 3 reputed fitness centers 83 cards of nourishing anamnesis and registry of 24 hours for analysis of the anthropometric variables: weight, height, index of corporal mass, besides the cost and total power consumption, as well as the qualitative nourishing consumption in 8 different nourishing groups according to the Brazilian Nourishing Pyramid. We observed total power consumption inferior to the cost in daily physical activities, accompanied by lowest ingestion by the groups of breads and milky cereals, vegetables, fruits and milk by products; and low consumption of the groups of leguminous and sugars. In global terms, our results have indicated feeding underthe recommendations both in quantitative and qualitative terms of those physically active women; thus, in future deployments, a more reliable and representative instrumentfor habitual consumption must be used in order to confirm the assumptions formulated in this exploratory study. As nutritional recommendation for that group, it would be desirable to increase power coming from the consumption of the group of breads and cereals, milk, and FLV (fruits, leguminous and vegetables), whose register is agreed, according to diverse national and international directives, with nutritional adjustment for quality of life and maintenance of a physically active life style.